Pengembangan Desa Wisata Berbasis Pemberdayaan Masyarakat di Desa Wisata Simathani Marurup Kabupaten Tulungagung - Sofhiana Sinta Devi; Tjitjik Rahaju (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The development of tourism villages is an effective strategy to support environmental conservation and empower local communities. This study aims to describe the development of Simathani Marurup Tourism Village in Tulungagung Regency based on community empowerment. A descriptive qualitative method was employed, using four tourism village development indicators proposed by Prakoso (2022): setting, management, resources, and benefits, along with community empowerment approaches outlined by Widjajanti (2011). The findings indicate that the village has successfully utilized its geographical and cultural potential, with active community participation in management and partnerships with the government. Empowerment strategies applied include problem-based, need-based, rights-based, and asset-based approaches. The economic impact has begun to emerge, although distribution remains uneven. This study emphasizes the importance of integrating local potential with empowerment approaches to create an inclusive, participatory, and sustainable tourism village. Recommendations focus on strengthening the role of local government in training, funding, and supportive policy formulation.